Conceptual framework of acoustic comfort design enablers for a classroom : A systematic review - Abdul Wafi, Razali; Nazli, Che Din; Musli Nizam, Yahya; Raha, Sulaiman (Elsevier, 2024)
Effective communication between instructors and students is crucial for facilitating the teaching and learning process. Multiple studies have demonstrated that classroom acoustic conditions impact students' academic achievement and the teachers' overall well-being. The acoustic comfort of a classroom is impacted by multiple aspects that must not be disregarded. Although there have been several studies on classroom acoustics, there is a shortage of thorough reviews that examine the impact of design factors in predicting acoustic quality. The aim of this study is to develop a conceptual framework for classroom acoustic comfort that encompasses the objectives of i) identifying various design enablers that may contribute to optimal acoustic comfort for learning purposes and ii) analysing the influence of each design enabler on significant acoustic parameters for classrooms. An analysis of 74 publications was carried out to examine the effects of various classroom design factors on acoustic performance. The study identifies six design enablers for classroom acoustic comfort: material, volume, layout, amplification system, noise, and occupancy and five acoustic parameters: reverberation time, background noise, signal-to-noise ratio, speech transmission index and speech clarity. A conceptual framework is proposed for designers, researchers, and end-users to consider the enablers’ roles in creating an optimal classroom learning environment.